Effect of Zinc Deficiency on Haematological Parameters and Mineral Contents of Selected Tissues in Albino Rats - Ajayi, O.B. (Pakistan Journal of Nutrition, 2008)
The effect of zinc deficiency on tissue level of some minerals (Na, K, Ca, P, Cu, Fe, Mg, Zn, Mn) in growing rats was investigated. Two groups of rats were fed either a zinc adequate diet or zinc deficient diet (6 ppm) for six weeks. At the end of the feeding period, zinc deficiency decreased the final body weight of the rats by 70% compared to the control. There was no significant difference (P < 0.05) in the packed cell volume (PCV) and the white blood cell count (WBC) of the zinc deficient rats was significantly increased (P < 0.05) compared to the control. Tissue content of minerals measured in the liver and kidney of both group of rats showed that zinc deficiency significantly increased (P < 0.05) tissue concentration of some elements (Fe, Cu, Ma, Ca, K and Na) while Mg and phosphorus levels were lowered compared to the control. This result suggest that zinc deficiency in rats could have adverse effect on intermediary metabolism as a result of interplay in the interactions between these minerals.